Bureaucracy in Perspective of Government Administration Laws - Diniyanto, Ayon (Law Research Review Quarterly, 2020)
This paper discusses bureaucracy in the analysis of law number 30 of 2014 concerning government administration as a form of democracy implementation. However, bureaucracy in many cases shows a negative tendency (corrupt behavior, including collusion and nepotism). Various forms of bureaucracy in Indonesia in history were also formed on the basis of the regime and the tastes of the authorities. So that various negative behaviors tend to occur. This paper is a normative legal study in which the writer only analyzes based on the laws and regulations and related legal theories. This paper confirms that law number 30 of 2014 concerning government administration has explicitly set the efforts that must be made by the government in resolving various issues relating to the administration of government and bureaucracy.